2000
DOI: 10.1023/a:1007678404911
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To study delivery outcome in women with asthma, using Swedish health registers. Women with asthma were identified in two ways: by information in interviews performed by midwives at the pregnant woman's first visit to antenatal care, and by linkage between a medical birth register and a hospital discharge register, identifying women who had been hospitalized for asthma and also had a delivery. Births between 1984 and 1995 were studied. An increased risk for preterm birth and low birth weight was seen, possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The adverse impact of asthma in pregnancy on most outcomes is striking. Although increased risks of haemorrhage during pregnancy, premature contractions, placental abruption and SGA have been observed in some previous studies [5], [6], [9], [12][14], [28][30], the novelty with our results is the consistency in risk increases for women with asthma before and during pregnancy across all pregnancy and labour characteristics, as well as most perinatal outcomes. This has not been previously shown and has important public health implications.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The adverse impact of asthma in pregnancy on most outcomes is striking. Although increased risks of haemorrhage during pregnancy, premature contractions, placental abruption and SGA have been observed in some previous studies [5], [6], [9], [12][14], [28][30], the novelty with our results is the consistency in risk increases for women with asthma before and during pregnancy across all pregnancy and labour characteristics, as well as most perinatal outcomes. This has not been previously shown and has important public health implications.…”
Section: Discussionsupporting
confidence: 61%
“…Maternal asthma has been associated with an increased risk for pregnancy complications such as preeclampsia, gestational diabetes, premature contractions and premature ruptures of membranes [5][8]. Maternal asthma has also been associated with an increased prevalence of labour characteristics including caesarean section and placental abruption [9][12], or perinatal outcomes such as low birth weight, prematurity and small for gestational age (SGA) [6], [12][15] but studies are also non-consistent [2], [7], [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that asthma severity prior to pregnancy is associated with uncontrolled asthma status during pregnancy 1 , and this may result in adverse pregnancy outcomes, such as preterm birth and low birth weight 2 . The aims of our study were four-fold: To examine 1) whether the prevalence of uncontrolled asthma, assessed by the Asthma Control Test (ACT) during pregnancy is consistent with prior estimates; 2) whether baseline uncontrolled asthma status evaluated by ACT at subjects’ enrollment (10–18 weeks of gestation) would be associated with increased risk of uncontrolled asthma during the remainder of pregnancy; 3) whether serum vitamin D level (25OHD) is associated with asthma control status at enrollment; 4) whether body mass index (BMI) at enrollment affects the relationship of 25OHD and asthma control status at enrollment and during pregnancy.…”
Section: To the Editormentioning
confidence: 99%
“…54 Furthermore, exposure of these mice to the natural antagonist of IL-1 (IL-1 receptor antagonist) abrogates parturition; 55 3) extra uterine infection resulting in systemic inflammation such as malaria, 56;57 pyelonephritis, 58–60 pneumonia 61;62 and periodontal disease 63;64 have been associated with preterm birth; and 4) non-infectious chronic inflammatory disorders like systemic lupus erythematosus, 65;66 inflammatory bowel diseases, 6769 asthma, 70;71 and morbid obesity 7274 have been associated with preterm parturition.…”
Section: Introductionmentioning
confidence: 99%